2019
DOI: 10.1101/607275
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

2’, 3’, 4’-trihydroxychalcone is an Estrogen Receptor Ligand Which Modulates the Activity of 17β-estradiol

Abstract: Menopausal hormone therapy (MHT) reduces the risk of osteoporosis, fractures, obesity and diabetes, but longterm MHT increases risk of other diseases. Safe long-term MHT that exploits its benefits and abrogates its adverse effects requires a new approach. Here we demonstrate that 2', 3', 4'-trihydroxychalcone (CC7) acts as an estrogen receptor alpha (ERα) ligand that may improve the safety profile of MHT. CC7 reprograms the actions of estradiol (E2) to regulate unique genes in bone-derived U2OS cells, with 824… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 43 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…In silico studies performed with the chalcone 2′,4′dihydroxy-6-methoxy-3,5-dimethylchalcone (44) (Figure 9), a component of the leaves of Eugenia aquea established its interaction with estrogen receptor α [45,46]. Another similar virtual screening of 2′,3′,4′-trihydroxychalcone (45) showed that this chalcone acted as an estrogen receptor ligand that could modulate the activity of 17β-estradiol [47]. 43), was proposed as useful against prostate cancer as it was noted to cause cell cycle arrest and apoptosis (Figure 7) [43].…”
Section: Binding With the Estrogenic Receptor (Er)mentioning
confidence: 99%
See 2 more Smart Citations
“…In silico studies performed with the chalcone 2′,4′dihydroxy-6-methoxy-3,5-dimethylchalcone (44) (Figure 9), a component of the leaves of Eugenia aquea established its interaction with estrogen receptor α [45,46]. Another similar virtual screening of 2′,3′,4′-trihydroxychalcone (45) showed that this chalcone acted as an estrogen receptor ligand that could modulate the activity of 17β-estradiol [47]. 43), was proposed as useful against prostate cancer as it was noted to cause cell cycle arrest and apoptosis (Figure 7) [43].…”
Section: Binding With the Estrogenic Receptor (Er)mentioning
confidence: 99%
“…In silico studies performed with the chalcone 2 ,4dihydroxy-6-methoxy-3,5-dimethylchalcone (44) (Figure 9), a component of the leaves of Eugenia aquea established its interaction with estrogen receptor α [45,46]. Another similar virtual screening of 2 ,3 ,4 -trihydroxychalcone (45) showed that this chalcone acted as an estrogen receptor ligand that could modulate the activity of 17β-estradiol [47]. Branham et al [48] used the estrogen receptor-ligand binding assay to assess the relative binding affinity of five chalcones, i.e., chalcone (1), 4-hydroxychalcone (20), 4′-hydroxychalcone (21), phloretin (23), and 4,2′,4′-trihydroxychalcone (46), and a significant level of binding with the estrogen receptor α was observed with all these chalcones.…”
Section: Binding With the Estrogenic Receptor (Er)mentioning
confidence: 99%
See 1 more Smart Citation